2021
DOI: 10.1155/2021/1458373
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Emission Measurement and Its Spatiotemporal Evolution of Tourism Industry in Heilongjiang Province, China

Abstract: This study analyses the composition and evolution of carbon dioxide emissions from the tourism industry in Heilongjiang Province and its 12 regions by the tourism consumption stripping coefficient method and calculates the decoupling relationship between the carbon dioxide emissions and economic growth of tourism from 2010 to 2019. The empirical results are as follows. (1) From 2010 to 2019, carbon dioxide emissions from Heilongjiang Province’s tourism industry and its subsector increased steadily, of which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…In this study, the TCDEE of Heilongjiang averaged 0.9007 in the sample period, which is close to the optimal frontier. erefore, our conclusion that Heilongjiang had a relatively high TCEDD can be strongly supported by Tang and Huang's results [34].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study, the TCDEE of Heilongjiang averaged 0.9007 in the sample period, which is close to the optimal frontier. erefore, our conclusion that Heilongjiang had a relatively high TCEDD can be strongly supported by Tang and Huang's results [34].…”
Section: Discussionsupporting
confidence: 79%
“…This effort drives the low-carbon development of tourism. Taking Heilongjiang as an example, Tang and Huang [ 34 ] studied the detachment between carbon dioxide emission and tourism economy growth in 2019 and found that the detachment is basically benign. Thus, they concluded that energy conservation and emission reduction measures have achieved certain effects on promoting the tourism development in Heilongjiang.…”
Section: Resultsmentioning
confidence: 99%